Brave New Worlds. Shakespearean Tempests in Italian Prisons (Altre Modernità, 2017)
Shakespeare is a pivotal and much staged playwright by theatre companies of prisoners in Italy, even though the practice of theatre in prison in Italy has a much shorter tradition than in the Anglo-Saxon world. Among the many Shakespearean plays, "The Tempest" is a favourite, being obviously able to shine a new light on the themes of revenge, freedom and forgiveness that are central issues in a prison context. Undeniably, in Italy, productions of "The Tempest" in prison have deeply instilled new life into the staging of the Elizabethan playwright. The list includes different kinds of experiences ranging from drama therapy, where the process towards rehabilitation and reintegration is more important than the finished aesthetic product, to productions by theatre directors who are primarily concerned with the artistic medium of the theatre and its aesthetic qualities. A survey of Shakespeare theatrical practice in Italian prisons can help investigate and understand not only the aesthetic but also the political, social and economic consequences of the function of prison nowadays, and provides the first step towards an analysis of Shakespeare practice in Italian prisons in a broader context. By comparison with other European countries, we may also discover that some Italian experiences, such as Fabio Cavalli's work in Rome at the Rebibbia prison, or Armando Punzo's with the "Fortress Company" in Volterra are unique and they deserve more attention.